Islam Wasatiyah as a Form of Religious Moderation: Values, Challenges, and Implementation in Indonesia - Ainun Nafisa; Alpin Iskandar; Bayu Nugraha (Bulletin of Islamic Research, 2023)
Religious moderation is a concept that is rooted in the word "moderate," which means to be in the middle, not excessive, and not lacking. In the context of Islam, this moderation is known as "Wasatiyah Islam," which prioritizes the principles of justice, balance, and equality. This concept is reflected in the Qur'an, especially in Surah Al-Baqarah verse 143, which emphasizes the importance of being a people who are in a middle, just, and balanced position. This research aims to explore the core values of religious moderation, including tolerance (tasamuh), justice (i'tidal), balance (tawazzun), and equality, as well as how these values are internalized through education and social practice. In addition, this study also analyzes the challenges in implementing the principles of religious moderation in Indonesia, including geopolitical influences and socio-religious dynamics influenced by globalization. The findings of this study are expected to contribute to strengthening the narrative of Islam Wasatiyah as a strategy to prevent extremism and maintain religious harmony in Indonesia.